2015
DOI: 10.1111/jfpp.12689
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Quality Indicators of Taste and Infusion Color and Discrimination of Famous and Superior Green Tea with Different Appearances in Fujian Province, PR China

Abstract: Compared to traditional sensory quality evaluation, chemical components and color values in CIE-Lab space are looked as indicators to assess tea quality objectively. This study spectrophotometrically analyzed quality indicators of famous and superior green tea (FSGT) with three appearance types in the Fujian Province, PR China and applied chemometrics methods to discriminate them. By factor analysis, all indicators were classified into four factors, evaluating FSGT quality in (1) lightness, yellowness and satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The Longjing teas with scores above 90 were positively correlated with overall quality and five sensory factors based on QDA. The results were in agreement with previous studies, which reported that special‐grade green teas (total sensory scores ≥90) are characterized by super‐excellent appearance features, bright and green tea infusion, high and pleasant aroma, and umami taste, due to their rigorous harvest season, harvesting standard and delicate processing (Guo & Lai, 2016; Li et al, 2019). In a word, traditional QDA was an effective tool to distinguish tea overall quality grade; however, tea flavor characterization could not work.…”
Section: Resultssupporting
confidence: 92%
“…The Longjing teas with scores above 90 were positively correlated with overall quality and five sensory factors based on QDA. The results were in agreement with previous studies, which reported that special‐grade green teas (total sensory scores ≥90) are characterized by super‐excellent appearance features, bright and green tea infusion, high and pleasant aroma, and umami taste, due to their rigorous harvest season, harvesting standard and delicate processing (Guo & Lai, 2016; Li et al, 2019). In a word, traditional QDA was an effective tool to distinguish tea overall quality grade; however, tea flavor characterization could not work.…”
Section: Resultssupporting
confidence: 92%
“…Meizhan (MZ, No. GS13004-1985, Chinese Crop Varieties Examining Committee, 1985) is also good for making HSGT and other green teas [10] due to its robust taste and high scores in sensory evaluations [11,12]. In addition, Qingliang Mountain tea (QL), a local Guangdong variety grown mainly in the Qingliang Mountains of Meizhou where there is a long history of making HSGT, produces the representative fried rice fragrance when properly processed.…”
Section: Introductionmentioning
confidence: 99%
“…Meizhan is one of the most widely cultivated varieties in China, with rich aroma components and widely processing suitability [ 16 , 17 ]. Aim to disclose the impact of tea processing method on phytochemicals of tea and explore the potential health effect of various teas, meanwhile, minimize the influence of material differences.…”
Section: Introductionmentioning
confidence: 99%